Solve the equation 39x-18x+-12x+14x=-60x-657x+256

14x-12x+39x-18x=256-60x-657x

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

$x=\frac{64}{185}$

Step by step solution

Problem

$14x-12x+39x-18x=256-60x-657x$
1

Adding $14x$ and $-12x$

$21x+2x=256+\left(-60-657\right)x$
2

Subtract the values $-60$ and $-657$

$21x+2x=256-717x$
3

Adding $2x$ and $21x$

$23x=256-717x$
4

Grouping terms

$717x+23x=256$
5

Adding $23x$ and $717x$

$740x=256$
6

Multiply both sides of the equation by $$

$x=\frac{64}{185}$

Answer

$x=\frac{64}{185}$

Problem Analysis

Main topic:

Equations

Time to solve it:

0.27 seconds

Views:

178